Relationship Between Ante Natal Care As A Health Education Approach And Incidence Of Hypertension (Gestational Hypertension) Among Pregnant Women - Dewi Atika Putri; Hari Iskandar Kang; Anindini Winda Amalia; Iwan Kusnawirawan; Hernayati Hernayati; Muhammad Arsyad Subu (Syntax Corporation Indonesia, 2023)
This study aims to determine the relationship between antenatal care (ANC) education approach and the incidence of hypertension in pregnant women. This study used a descriptive method to understand the relationship between the ante natal care as a health education approach and the incidence of hypertension in pregnant women. Samples were randomly taken on pregnant women who visited Antenatal Care in Leuwiliang district with a correlation formula as a minimal calculation. Eighty-seven subjects were included, and blood pressure measurements were carried out following the SOP for blood pressure measurement with description analysis and analysis of the relationship between hypertension events with ANC visits and gestational age. The highest variable of antenatal care visits in incomplete visits was 66 pregnant women (66.0%). Pregnant women who have the most hypertension status were 55 pregnant women (55.0%). The most hypertension in the group was not at risk as much as 46%. The highest percentage were mothers whose antenatal care visits were incomplete and hypertension was 44%. The lowest percentage is mothers with complete antenatal care visits and normal hypertension which was 8%. There was an incidence of hypertension in the non-risk group and ANC visits and showed the presence of hypertension in the incomplete ANC visit group. Thus, educational approaches and efforts to increase awareness of pregnant women in ANC need to be improved